Diseño de la documentación del sistema de gestión en seguridad y salud en el trabajo con base en el Decreto 1072 del 2015 para la empresa Cermac sas en la ciudad de Bogotá (2022)
The objective of this document is to design documentation of safety and health at work health and safety at work management system in the company Cermac SAS, under the requirements of Decree 1072 of 2015. Decree 1072 of 2015, the type of research is mixed given that it analyzes the quantitative and qualitative. For the development of the document, data was collected and analyzed through an initial diagnosis based on the regulations. Based on the regulations, we proceeded to make the risk matrix identifying the hazards that are in the organization for the hazards found in the organization to then continue with the intervention measures. intervention measures, as well as the design of the documentation based on Decree 1072 of 2015, such as, for example, the 2015, such as the emergency prevention plan, policy and objectives, procedures and instructions, among others, procedures and instructions, among others. With the above, the work seeks to establish an appropriate methodology for the compliance with the standard, considering the care of employees, visitors, contractors and other interested parties for the growth of the company, contractors and other interested parties for the growth and strength of the company.